2008
DOI: 10.1088/0022-3727/42/1/015208
|View full text |Cite
|
Sign up to set email alerts
|

Plasma heating effects in catalyzed growth of carbon nanofibres

Abstract: A theoretical model describing the plasma-assisted growth of carbon nanofibres (CNFs) that accounts for the nanostructure heating by ion and etching gas fluxes from the plasma is developed. Using the model, it is shown that fluxes from the plasma environment can substantially increase the temperature of the catalyst nanoparticle located on the top of the CNF with respect to the substrate temperature. The difference between the catalyst and the substrate temperatures depends on the substrate width, the length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…Table 1 summarizes the different mechanistic growth models published in recent years, indicating the processes included in each model, the reactor type (CVD or PE-CVD) and the simulation method. From this overview it is clear that the mechanistic models can be divided into three groups from simulation point of view, i.e., kinetic models [92][93][94][95][96][97][98][99], multiphysics, multiphase integrated models [100][101][102][103] and kinetic Monte Carlo (MC) models [104][105][106][107]. Puretzky and co-workers [92] presented a kinetic model for the CVD-based growth of vertically aligned nanotube arrays (VANTAs) from C 2 H 2 , based on in situ measurements.…”
Section: (B) Cnts and Related Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the different mechanistic growth models published in recent years, indicating the processes included in each model, the reactor type (CVD or PE-CVD) and the simulation method. From this overview it is clear that the mechanistic models can be divided into three groups from simulation point of view, i.e., kinetic models [92][93][94][95][96][97][98][99], multiphysics, multiphase integrated models [100][101][102][103] and kinetic Monte Carlo (MC) models [104][105][106][107]. Puretzky and co-workers [92] presented a kinetic model for the CVD-based growth of vertically aligned nanotube arrays (VANTAs) from C 2 H 2 , based on in situ measurements.…”
Section: (B) Cnts and Related Structuresmentioning
confidence: 99%
“…The model by Denysenko and Ostrikov [97,98] for the PECVD of CNFs also accounts for adsorption and desorption of C 2 H 2 and H, surface and bulk diffusion, incorporation into a graphene sheet, as well as ion-and radical-assisted processes on the catalyst surface that are unique to a plasma environment. It is shown that plasma ions play a key role in the carbon precursor dissociation and surface diffusion, enabling a low-temperature growth of carbon nanostructures.…”
Section: (B) Cnts and Related Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous works have been done to highlights the role of temperature on the growth of CNTs. [8][9][10][11][12][13][14][15] Han et al 8 have demonstrated that as the growth temperature increases, the average diameter of CNTs increased from 40 to 110 nm and the growth rate was enhanced from 2 to 15 lm/h. Baratunde et al 9 have shown that as the growth temperature was decreased, the associated decrease in CNT density and average CNT diameter resulted in an increased thermal resistance at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of catalyst, growth temperature, and the density of participating species, etc., have been extensively studied. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Sodha et al 1 in their theoretical model, have investigated the growth of embryonic dust particles in a complex plasma and found that the radius of the embryonic dust grains decreases with the number density of dust particles.…”
Section: Introductionmentioning
confidence: 99%